China's Carbon Trading Market Globalization Strategy: A Conceptual Review - Guangnan, Huang; Wai Yie, Leong (INTI International University, 2024)
China has once participated in the international carbon market through the Clean Development Mechanism (CDM) faced problems such as falling certified emission reductions (CER) prices and carbon sink fraud, which led to the decline of China's carbon trading market. However, with China's announcement of the goal of peaking carbon emissions before 2030 and achieving carbon neutrality before 2060, China's carbon market has regained vitality and launched China Certified Emission Reductions (CCER) as the main trading product. The study discusses the opportunities and challenges of China in the globalization of the carbon trading market, including key obstacles such as differences in rules and inconsistent carbon absorption measurement methods. At the same time, the paper proposes strategies such as connecting China's carbon trading market with the global market through the Hong Kong platform, strengthening international cooperation, optimizing market mechanisms, and improving technological innovation capabilities to promote the deep integration and coordinated development of China's carbon trading market with the international market. It emphasizes China's position and role in the global carbon trading system in the future, as well as its positive role in promoting global low-carbon transformation and international exchanges and cooperation.